1998
DOI: 10.1200/jco.1998.16.9.3137
|View full text |Cite
|
Sign up to set email alerts
|

A single scale for comparing dose-intensity of all chemotherapy regimens in breast cancer: summation dose-intensity.

Abstract: A single-agent dose-response database can be derived from historic literature that enables comparison of the dose-intensity of all combination regimens on one scale. The dose-intensity increase required to improve outcome can then be identified in earlier trials that tested that variable. SDI methodology should be tested prospectively in contemporary patients, and may be useful in guiding dosage increases beyond the conventional range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
6

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(62 citation statements)
references
References 56 publications
0
56
0
6
Order By: Relevance
“…The majority of our patient population had early stage disease, but around a third had metastases. The benefit of delivering full RDI to late-stage patients is less clear; it could lead to prolonged life [7], but this must be balanced against toxicity to the patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of our patient population had early stage disease, but around a third had metastases. The benefit of delivering full RDI to late-stage patients is less clear; it could lead to prolonged life [7], but this must be balanced against toxicity to the patient.…”
Section: Discussionmentioning
confidence: 99%
“…While the relative dose intensity (RDI) achieved may reflect underlying patient factors such as age and co-morbidity, data from studies in the adjuvant setting suggest that failure to receive planned dose contributes to poorer survival [3][4][5]. Ensuring optimal RDI is also a consideration in patients with metastatic disease when the aim of treatment is to prolong life [6,7]. Recent evidence-based guidelines issued by the European Organisation for…”
Section: Introductionmentioning
confidence: 99%
“…High-dose chemotherapy with haematopoietic support should be administered early, in a multicycle outpatient programme, and should be epirubicine based. Several questions remain open, such as the eventual role of taxanes in HDC protocols, even if a dose-response effect has not been clearly demonstrated for this family of cytotoxic agents (Hryniuk et al, 1998), and the role of newly available therapies such as anti Her2/neu antibodies. Large clinically relevant and well designed cooperative randomized trials addressing these different issues are still awaited.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive literature reviews by Hryniuk et al 1,2 have found dose intensity to be correlated with response rate and survival. This effect has been considered in the rationale of many clinical trials that attempted to improve long-term survival in metastatic BC by delivering single courses of high-dose chemotherapy (HDC).…”
mentioning
confidence: 99%